2021
DOI: 10.3390/microorganisms9010089
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Classifying Root Causes of Outbreaks of Legionnaires’ Disease: Deficiencies in Environmental Control and Water Management

Abstract: We piloted a methodology for collecting and interpreting root cause—or environmental deficiency (ED)—information from Legionnaires’ disease (LD) outbreak investigation reports. The methodology included a classification framework to assess common failures observed in the implementation of water management programs (WMPs). We reviewed reports from fourteen CDC-led investigations between 1 January 2015 and 21 June 2019 to identify EDs associated with outbreaks of LD. We developed an abstraction guide to standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…A separate review of legionellosis in VHA facilities between 2014 and 2016 found that healthcare-associated cases with overnight stays decreased . Together, these reports from VHA suggest the value of comprehensive Legionella primary prevention programs in improving patient safety, and align with insights from more focused outbreak reviews. , Further review to examine potential correlations between Legionella positivity in water and clinical cases is underway.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A separate review of legionellosis in VHA facilities between 2014 and 2016 found that healthcare-associated cases with overnight stays decreased . Together, these reports from VHA suggest the value of comprehensive Legionella primary prevention programs in improving patient safety, and align with insights from more focused outbreak reviews. , Further review to examine potential correlations between Legionella positivity in water and clinical cases is underway.…”
Section: Discussionmentioning
confidence: 98%
“…21 Together, these reports from VHA suggest the value of comprehensive Legionella primary prevention programs in improving patient safety, and align with insights from more focused outbreak reviews. 31,32 Further review to examine potential correlations between Legionella positivity in water and clinical cases is underway. The largest changes in positivity rates over the four years were observed for total Legionella and L. pneumophila (any serogroup).…”
Section: ■ Discussionmentioning
confidence: 99%
“…Building water management practices play an important role in controlling water quality in building water systems (Clopper et al, 2021;Logan-Jackson, A. R. and Rose, 2021), however building water management plans are typically developed on an ad-hoc basis using broad guidelines as a reference point rather than using a tailored site-specific approach (National Academies of Sciences, 2019). Given the need for and importance of comprehensive water management programs in large, commercial-institutional buildings and the human health threat from Legionella infection, it is crucial to assess the likelihood of a hazard and reduce exposures to ensure occupants' safety.…”
Section: Graphical Abstractmentioning
confidence: 99%
“…Water management plans are effective in reducing the likelihood of a Legionella spp. outbreak (Clopper et al, 2021). Several corrective actions were implemented by the building facility managers after they were informed about the deteriorating water quality during the duration of reduced occupancy.…”
Section: Impact Of Water Management Interventions On Building Water Q...mentioning
confidence: 99%
“…Inhalation of mist containing bacteria can also cause respiratory disease. Outbreaks of Legionnaires’ disease, for instance, are most often attributed to poor water treatment and infrastructure maintenance (e.g., infrequent cleaning of heating, ventilation, and air conditioning systems) in communities with centralized piped water networks ( 168 , 169 ). Finally, antibiotic-resistant bacteria in drinking water are also becoming increasingly common and pose significant health risks when resistance is transferred to human pathogens ( 170 ).…”
Section: Current Status Of Knowledgementioning
confidence: 99%